2016
DOI: 10.1186/s40360-016-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Side effect profile similarities shared between antidepressants and immune-modulators reveal potential novel targets for treating major depressive disorders

Abstract: BackgroundSide effects, or the adverse effects of drugs, contain important clinical phenotypic information that may be useful in predicting novel or unknown targets of a drug. It has been suggested that drugs with similar side-effect profiles may share common targets. The diagnostic class, Major Depressive Disorder, is increasingly viewed as being comprised of multiple depression subtypes with different biological root causes. One ‘type’ of depression generating substantial interest today focuses on patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Glucocorticoid receptor may be a therapeutic target for MDD patients because it is involved in both immune regulation and depression. Corticosteroids possibly restore the negative feedback loop on the hypothalamic–pituitary–adrenal axis to exhibit their antidepressive effects ( Sun et al, 2016 ). In a previous trial, the response rate of dexamethasone group could achieve 37%, while that of placebo group was only 6% ( Arana et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid receptor may be a therapeutic target for MDD patients because it is involved in both immune regulation and depression. Corticosteroids possibly restore the negative feedback loop on the hypothalamic–pituitary–adrenal axis to exhibit their antidepressive effects ( Sun et al, 2016 ). In a previous trial, the response rate of dexamethasone group could achieve 37%, while that of placebo group was only 6% ( Arana et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy study in this regard profiled drugs for their similarity across 4,201 side effects, and found that cytokine inhibitors were closest in the high-dimensional side effect space to drugs with a dopaminergic effect, but were distant from other antidepressants 148 . This finding suggests that dopaminergic compounds that influence reward-guided behaviours may be more effective in patients with an inflammatory component to their depression.…”
Section: Patient Stratificationmentioning
confidence: 99%
“…One study analyzing drug-similarity based on side effect profiles indicates indeed that some antidepressants and some immune-related drugs may affect common molecular pathways, such as cytokines levels and glucocorticoid signaling [85].…”
Section: First Line Treatments For Pediatric Ocd Clinical Moderators mentioning
confidence: 99%